Variability in the utilization of preventive dental services among the underserved population of Indiana - Anubhuti Shukla; Bhavya Vaishnavi Amrutham; Sheetal Manchanda (PLoS ONE, 2025)
Objectives To explore the variability of utilization patterns of preventive dental services among diverse demographic groups in the state of Indiana. Methods This study utilizes a retrospective data analysis approach to examine the preventive dental services utilization among patients treated by senior-year dental students (D4 students) during their community-based clinical rotations at Federally Qualified Health Centers and private practices, affiliated with Indiana University School of Dentistry. The data were extracted from daily patient reports submitted by D4 students for every patient they examined during their rotations, via RedCap. Descriptive statistics and generalized linear modeling using main effects were performed to identify the utilization of different preventive services across urbanization stratification and demographic variables among the included participants. Results There was a statistically significant (p < 0.001) distribution of all dental preventive services according to demographic characteristics, viz. age, ethnicity, location (rural or urban), primary language spoken, and insurance status. There were 30.39 times higher odds of utilizing preventive dental services in a rural zip code compared to an urban zip code. Individuals with multicultural ethnicities (OR= 0.91, 95% CI: 0.54, 1.53) were less likely to utilize preventive dental services than the “Other” category, although the value was not significant (p = 0.72). Also, the younger age group (less than 17 years) was more likely to utilize preventive dental services than the older age group (p < 0.001). Conclusions Inequities in the utilization of preventive dental services were identified among the underserved population of Indiana, according to demographic characteristics.